Effect of lumbopelvic myofascial force transmission on glenohumeral kinematics – A myo-fascia-biomechanical hypothesis - Leonard H. Joseph (2018)
© 2016 Warmińsko-Mazurska Izba Lekarska w Olsztynie Introduction The clinical management of shoulder disorders do not commonly includes the myo-fascial–skeletal contributions from the lumbopelvic (LP) region. Nevertheless, a notable myofascial–biomechanical connection exists between LP and shoulder regions. Aim The current paper proposes a quantifiable medical hypothesis that there will be an increased anterior humeral head translation (ATHH) in the glenohumeral joint (GHJ) due to altered myofascial force transmission that results from LP dysfunction. Material and methods A literature search was conducted in Science Direct and PubMed databases for articles published from January 1990 to December 2015. Medical Subject Headings and other keywords for search were myofascial continuity, force transmission, muscle slings, lumbopelvic-glenohumeral joint and biomechanics. Results and discussion The hypothesis suggests a clinical reasoning that impaired myofascial force transmission from LP region as one of the contributing factors for shoulder pathogenesis. The hypothesis is proposed based on the anatomical and biomechanical relationship between the LP region and the contralateral GHJ. Evidences of myofascial continuity between the LP and GHJ, myofascial force transmission and integrated energy transfer theory are explained to strengthen the proposed hypothesis. An experimental method to test the proposed hypothesis is recommended for researchers and clinicians. A theoretical understanding of the pre stressed spring system via the myofascial chains is applied to strengthen the reasoning on the current hypothetical connection between LP and contralateral GHJ. Conclusions The implication of the new medical hypothesis may substantiate the understanding of the clinicians on the connections between the LP and the contralateral GHJ to consider a global myo-fascial–skeletal management of shoulder disorders.